ADMINITRASI PEMERINTAHAN ISLAM : Studi Pemerintahan Kesultanan Buton Masa Muhammad Idrus Kaimuddin - HASARUDDIN (Jurnal Pendidikan Sejarah, 2024)
The Islamization of the archipelago influenced the development of the government system in most regions of the archipelago. The process of spreading and broadcasting peaceful Islam in various regions in the archipelago was accepted quickly and easily by society, especially in areas located on shipping and trade routes. Buton, which was on this route, easily accepted Islam, which then changed the government system from a kingdom with Islamic nuances to the status of a sultanate area. Apart from that, making Martabat Tujuh the philosophical foundation in running the government system. The Seventh Dignity which was made into a State Law became the basis for the formation of other regulations in structuring the State government system.